Pengaruh Suhu Fraksinasi terhadap Mutu Red Palm Oil - Khairiah, Hanifah (Politeknik Kampar, 2025)
Red Palm Oil (RPO) is one of the edible oil products derived from palm oil that retains its carotene content. Carotene is an important compound for the human body, as it functions as a provitamin A and also acts as a natural antioxidant. The production of RPO involves several stages, one of which is the fractionation process. This process is carried out to separate the liquid fraction (olein) from the solid fraction (stearin). If fractionation is not performed properly, a significant amount of stearin may remain in the RPO, causing the oil to become cloudy or solidify easily at temperatures below 25°C, including at room temperature. To date, literature examining the relationship between fractionation and the quality of RPO remains limited. Therefore, this study was conducted by varying the fractionation temperatures of RPO at 10°C, 15°C, 20°C, and 25°C. The purpose of these variations is to determine the optimal temperature for the fractionation process in order to produce high-quality RPO. The quality parameters of RPO analyzed in this study include: Free fatty acid (FFA) content, Moisture content, Carotenoid level, Iodine value, and Pelican oil.